KOLABORASI SEKOLAH DENGAN ORANG TUA DALAM MENINGKATKAN PROSES BELAJAR PESERTA DIDIK - Irwan Irwan; Nuryani Nuryani; Masruddin Masruddin (Kelola: Journal of Islamic Education Management, 2023)
This study aims to (1) describe the forms of school collaboration with parents in improving the learning process of students at SMP Negeri 2 Palopo, (2) To find out the implementation of collaboration between school management and parents in improving student learning outcomes at SMP Negeri 2 Palopo ( 3) To find out the factors that support and what factors become obstacles in the process of implementing collaborative school management with parents in improving student learning outcomes at SMP Negeri 2 Palopo.  This research is a qualitative descriptive research. Data collection techniques used are interviews, observation and document study. Data analysis techniques used are data reduction, data presentation and conclusion.  The results of the study show that the form and implementation of school collaboration with parents in improving the learning process of students at SMP Negeri 2 Palopo consists of: (a) Parenting Education. (b) Communication. (c) Parental Involvement. The supporting factor for school collaboration with parents is the existence of (a) educators who have a spirit of professionalism and responsibility for students. (b) the existence of supporting funds through BOS funds and so on (c) The school committee is one of those that supports the realization of collaboration between the school and parents to support the successful achievement of learning outcomes for students at SMP Negeri 2 Palopo. Furthermore, the inhibiting factors in the process of implementing school collaboration with parents in improving the learning process of students at SMP Negeri 2 Palopo include: (a) Time factor. (b) Parents' views of teachers. (c) Parents' self-confidence is still low